Serum lipid profiles of ovariectomized rats following short-term administration of cocoa powder and ethanolic extract. - Ariza Budi Tunjung Sari; Misnawi Misnawi; Pratiwi Pudjiastuti; Afaf Baktir (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2019)
Estrogen depletion increases the risk of dyslipidemia by triggering higher levels of total cholesterol (TC), triglyceride (TG), and low density lipoprotein (LDL) besides depressed level of high density lipoprotein (HDL). This study was conducted to investigate the potential of cocoa products to affect serum lipid profile in the estrogen-deficient rats. Thirty adult female wistar rats were divided into five groups i.e. four groups contained ovariectomized rats, and one group consisted of intact rats. The test articles were all dissolved in olive oil and administered orally, comprising of 1 g/kg body weight (BW) cocoa powder, 1 g/kg BW cocoa extract, 1 mg/kg BW estradiol valerate, 10 ml/kg BW olive oil as carrier. Intact group was given drinking water. After three-day administration, the rats were terminated and serum lipid profile was observed. The trial obtained ethical approval from the Animal Care and Use Committee, Veterinary Faculty, Airlangga University (Certificate No. 620-KE). The result showed that carrier group developed higher LDL and lower HDL levels, as well as greater LDL/HDL ratio compared to that of intact group. Estradiol valerate group had significantly elevated TG level. Cocoa powder and cocoa extract groups showed small and non-significant changes in TC, TG and HDL. Surprisingly, consumption of cocoa extract that is rich in polyphenols had resulted highest mean of LDL levels among other groups. It was hypothesized that polyphenol in cocoa extract had affected expression of LDL receptors (LDLR) due to an antagonistic activity against estrogen receptor alpha (ERá). To conclude, neither cocoa powder nor cocoa extract exhibits significant estrogenic effect on the serum lipid profile of estrogen-deficient rats.